PENGEMBANGAN PERANGKAT PEMBELAJARAN STATISTIKA DASAR BERMUATAN PENDIDIKAN KARAKTER DENGAN METODE PROBLEM BASED LEARNING - Fitri, Amalia (JPP, 2011)
This research is the development of learning tools, which aims to: (1) describe the developmentÃ¢â¬â¢sprocess and produce valid tools that contained character education on the ElementaryStatisticÃ¢â¬â¢s learning with Problem Based Learning methods; (2) To determine Effectiveleyresults the tools of learning. Those tools are developed by using the developmentmodel of Ploom. Field trials conducted on the elementary statistics learning atMathematics edacation program. Independent variables are motivation and process skills,while the dependent variable is the problem solving ability. The results showed the developmentÃ¢â¬â¢sprocess can produce valid tools learning and effective learning.Keywords: Character Education, Problem Based Learning, Tool Learning